PELUANG-PELUANG KARIER DALAM PENDIDIKAN JASMANI DAN OLAHRAGA: RELEVANSI LULUSANPROGRAM STUDI PJKR DENGAN KEBUTUHANMASYARAKAT - Joko Purwanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Discussing about Physical Education Health and Recreation study program’s curriculum2002 Sport Science Faculty Yogyakarta State University from content of curriculum andpurpose of study program dimension has aim to give a new perspective that physicaleducation and sport carrer is not only to be a physical education teacher in school. Careeropportunity that related with physical education and sport in society is various, even physicaleducation graduates could create their own career based in their academic potential andwhat they want. This perspective has a deep target. Implementation this perspective iscomplecated process. Thus, preparing of curriculum has to do as soon as possible.Identifying of career opportunity of physical education and sports graduates able to use asa consideration to improve physical education and sport curriculum.Kata Kunci: career, physical education, sport.